Lesson Study Through the Project-Based Learning Model to Improve Creative Thinking Ability - Pratiwi, Rani Tania; Rismawati, Rismawati; Nuryatin, Atin; Rosaline, Caecilia Dina; Suryani, Yeyen; Agustira, Deden (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Thinking creatively is crucial for students' academic and personal development. This study aims to analyze the impact of the Lesson Study-based Project-Based Learning (PjBL) model on the creative thinking skills of seventh-grade students in social studies at SMP Negeri 2 Cimahi. The research was motivated by students' low creative thinking ability, as indicated by their reliance on textbooks and lack of initiative in independent problem-solving. This study employed a quasi-experimental method with a non-equivalent control group design, involving two groups: an experimental group that received Lesson Study-based PjBL and a control group taught using the lecture method. Data were collected through pre-tests and post-tests, classroom observations, and documentation. The data analysis used quantitative statistical techniques to compare the improvement in students' creative thinking abilities. The results revealed a significant difference between the two groups, with the experimental group showing a higher increase in creative thinking skills, particularly in fluency, flexibility, originality, and elaboration. These findings suggest that the Lesson Study-based PJBL model is an effective instructional approach to foster student creativity. Future research should explore its long-term impact and potential application in other subjects and educational levels.